X‐ray diffraction using focused‐ion‐beam‐prepared single crystals. Issue 3 (14th April 2020) - Weigel, Tina; Funke, Claudia; Zschornak, Matthias; Behm, Thomas; Stöcker, Hartmut; Leisegang, Tilmann; Meyer, Dirk C.
Abstract : This study demonstrates a new preparation method for single‐crystal X‐ray diffraction samples using a focused ion beam. The results of the structure determination and electron density maps with differently prepared samples are discussed, to evaluate this new method. Abstract : High‐quality single‐crystal X‐ray diffraction measurements are a prerequisite for obtaining precise and reliable structure data and electron densities. The single crystal should therefore fulfill several conditions, of which a regular defined shape is of particularly high importance for compounds consisting of heavy elements with high X‐ray absorption coefficients. The absorption of X‐rays passing through a 50 µm‐thick LiNbO3 crystal can reduce the transmission of Mo  K α radiation by several tens of percent, which makes an absorption correction of the reflection intensities necessary. In order to reduce ambiguities concerning the shape of a crystal, used for the necessary absorption correction, a method for preparation of regularly shaped single crystals out of large samples is presented and evaluated. This method utilizes a focused ion beam to cut crystals with defined size and shape reproducibly and carefully without splintering. For evaluation, a single‐crystal X‐ray diffraction study using a laboratory diffractometer is presented, comparing differently prepared LiNbO3 crystals originating from the same macroscopic crystal plate. Results of the data reduction, structure refinement and electron density reconstruction indicate qualitatively similar values for all prepared crystals. Thus, the different preparation techniques have a smaller impact than expected. However, the atomic coordinates, electron densities and atomic charges are supposed to be more reliable since the focused‐ion‐beam‐prepared crystal exhibits the smallest extinction influences. This preparation technique is especially recommended for susceptible samples, for cases where a minimal invasive preparation procedure is needed, and for the preparation of crystals from specific areas, complex material architectures and materials that cannot be prepared with common methods (breaking or grinding).